Negotiating Islamic Marriage Values in the Digital Age: An Analysis of Generation Z Muslims through the Lens of Maqashid al-Usrah - Fadhilah, Nur; Masruchah, Siti; Sa'adah, Mazro'atus; Hidayati, Nuril; Ashfiya, Hamadah (Universitas Islam Sultan Agung, 2025)
Digital platforms have increasingly reshaped the ethical and relational landscape of Muslim youth, raising concerns about how online environments influence their understanding of Islamic values, particularly in relation to marriage. In response to this issue, the present study investigates how Muslim Generation Z interprets and negotiates Islamic marital ideals within the digital sphere, focusing on TikTok as a contested arena for ethical and religious discourse. Guided by Jamaluddin Athiyah's framework of maqashid al-usrah, the research explores how Muslim Generation Z constructs and represents marriage values—including affection and mercy, financial maintenance, protection from harm, and justice within the household—and how algorithmic mediation influences these interpretations. Employing a qualitative design that combines netnography, discourse analysis, and in-depth interviews with 15 informants, this study integrates digital observations and documentary evidence. The findings reveal that TikTok serves both as a platform for ethical affirmation and as a site of normative distortion: while affection and mercy are expressed through acts of care, financial anxieties and distorted portrayals of patience risk normalising injustice. The novelty of this study lies in the application of maqashid al-usrah to digital ethnography, offering new insights into the intersection of Islamic ethics and algorithmic culture. Scientifically, it contributes to the field of Islamic family law studies by demonstrating the adaptability of maqashid-based frameworks to digital contexts. The study recommends promoting digital literacy rooted in Islamic ethics to strengthen family resilience and safeguard moral integrity in the digital age.